Pengendalian Persediaan Spare Part Menggunakan Metode ABC dan Probabilistik Continuous System (Q) di PT. XYZ - Nurcahyo, Fajar; Lahay, Idham Halid; Uloli, Hendra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Inventory control is a very important managerial function because physical inventory usually involves the largest capital investment in current assets for many companies. Therefore, inventory must be managed and recorded well so that the company can sell its products and generate revenue, thus achieving the company's goals. With inventory, companies are able to carry out the production process continuously and avoid shortages of goods and delays in meeting customer demand, which can be detrimental to the company. Not optimal control of spare parts inventory can result in inventory shortages (out of stock). This study aims to optimize inventory with the ABC method and the probabilistic model Q. The results show the classification of spare parts into categories A (41%, 81%), B (18%, 10%), and C (41%, 9%). The Model Q reduces inventory costs by IDR 295 million. This study provides practical recommendations for inventory management in the automotive industry.